Synthesis of Nitrogen-Doped Carbon Nanocoils with Adjustable Morphology using Ni–Fe Layered Double Hydroxides as Catalyst Precursors - Tomohiro Iwasaki; Masashi Tomisawa; Takuma Yoshimura; Hideya Nakamura; Masao Ohyama; Katsuya Asao; Satoru Watano (Nanomaterials and Nanotechnology)
Nitrogen-doped carbon nanocoils (CNCs) with adjusted morphologies were synthesized in a one-step catalytic chemical vapour deposition (CVD) process using acetoni‐ trile as the carbon and nitrogen source. The nickel iron oxide/nickel oxide nanocomposites, which were derived from nickel–iron layered double hydroxide (LDH) precur‐ sors, were employed as catalysts for the synthesis of CNCs. In this method, precursor-to-catalyst transformation, catalyst activation, formation of CNCs, and nitrogen doping were all performed in situ in a single process. The morphology (coil diameter, coil pitch, and fibre diameter) and nitrogen content of the synthesized CNCs was indi‐ vidually adjusted by modulation of the catalyst composi‐ tion and CVD reaction temperature, respectively. The adjustable ranges of the coil diameter, coil pitch, fibre diameter, and nitrogen content were confirmed to be approximately 500±100 nm, 600±100 nm, 100±20 nm, and 1.1±0.3 atom%, respectively.